PEMBATASAN JUMLAH PEMBUATAN AKTA NOTARIS OLEH DEWAN KEHORMATAN PUSAT IKATAN NOTARIS INDONESIA - Heni Kartikosari; Rusdianto Sesung (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
To protect the Notary Public Offices and the people who use Notary services related to the legal certainty of the deed made by the Notary, the Central Board of Trustees of the Indonesian Notaries Association issued the Regulation of the Central Board of Honor No. 1 of 2017 on the Fairness Limit of Number of Permanent Deeds. The regulation is determined by the Central Board of Trustees that the limit of fairness in the deed per day is 20 (twenty) deeds.